Distribution of 137Cs and 40K in the tissue of silver fir trees (Abies alba Mill.) from Lika (Croatia) : Distribucija 137Cs I 40K u tkivima stabala obične jele (Abies alba Mill.) iz Like (Hrvatska) - Popijač, Marina (Array, 2021)
The research on activities of 137Cs and 40K, which was conducted on the silver fir (Abies alba Mill.) from Lika has included sampling of the trees in the field (rings of the bole from three different heights separated into bark, growth rings, roots, needles, shoots, and the soil surrounding the cut down trees), laboratory analysis of samples using the gamma-ray spectrometry and the statistical analysis of the collected data. The radial and vertical distribution of cesium (137Cs) in trees was investigated. 137Cs has contaminated forest ecosystems by remote atmospheric transport and radioactive precipitation as a result of nuclear test including the nuclear accident in Chernobyl. On a longer time scale, the variability of the 137Cs distribution determined in the organisms of the silver fir depended on the half-life, while the seasonal dynamics were influenced by the degree of physiological activity and the characteristics and functions of plant tissues. The highest activity of 137Cs was determined in the bark and the physiologically most active parts of the silver fir (shoots and needles). The highest activity concentration of the 137Cs in the growth rings was measured in the lowest parts of the silver fir trees. This research contributed to understanding the behavior of 137Cs, which entered the organisms of dominant tree species in the forest ecosystem, as well as its distribution in time and space.